2014
DOI: 10.1371/journal.pone.0108662
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell Secreted Sphingosine 1-Phosphate (S1P) Exerts a Stimulatory Effect on Skeletal Myoblast Proliferation

Abstract: Bone-marrow-derived mesenchymal stromal cells (MSCs) have the potential to significantly contribute to skeletal muscle healing through the secretion of paracrine factors that support proliferation and enhance participation of the endogenous muscle stem cells in the process of repair/regeneration. However, MSC-derived trophic molecules have been poorly characterized. The aim of this study was to investigate paracrine signaling effects of MSCs on skeletal myoblasts. It was found, using a biochemical and morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 62 publications
2
33
0
Order By: Relevance
“…This may possibly be due to a crosstalk with other growth factor receptors present in the releasate such as EGFR when used in high concentrations . This notion is strengthened by previous studies showing that PDGF/VEGF inhibition resulted in diminished myoblast proliferation and recombinant PDGFs improved skeletal muscle recovery after injury …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This may possibly be due to a crosstalk with other growth factor receptors present in the releasate such as EGFR when used in high concentrations . This notion is strengthened by previous studies showing that PDGF/VEGF inhibition resulted in diminished myoblast proliferation and recombinant PDGFs improved skeletal muscle recovery after injury …”
Section: Discussionmentioning
confidence: 93%
“…Given the above observations that mRNA and protein levels of PDGF and VEGF are increased in proliferating myoblasts (Figure ), as well as their abundance in the releasate (Figure ), we reasoned that these growth factors may be governing cell proliferation, as shown when individually targeted . To further investigate this notion, we used low, medium and high doses of VEGFR or PDGFR Inhibitors with or without releasate to assess C2C12 cell proliferation (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…A schematic diagram showing a skeletal muscle stem cell's (ie, satellite cell) possible response to growth factors, based on current published evidence . Located between the basal lamina and the sarcolemma of the muscle fibre, the satellite cell may come into contact with hundreds of growth factors and cytokines in response to platelet‐rich plasma ( PRP ) administration.…”
Section: Overview Of Platelet Biologymentioning
confidence: 99%
“…Some of the cell types in Table include myogenic progenitor cells, bone‐derived periosteal cells, osteosarcoma, endothelial, trabecular bone cells, human adipose‐derived mesenchymal stem cells, fibroblasts, tenocytes, myo‐endothelial cells, pericytes, C2C12 cells, adipose‐derived stem cells and muscle satellite cells. Variable levels of differentiation have been reported for different cell types, for example increased differentiation for rat bone marrow cells, human skeletal muscle myoblasts, rat muscle satellite cells, rabbit bone marrow mesenchymal stem cells and C2C12 myoblasts or maintained effect with hMDPCs, myo‐endothelial cells and pericytes compared to control conditions . Conversely, some studies reported that platelets inhibited differentiation of C2C12 myoblasts .…”
Section: Platelet‐mediated Skeletal Muscle Regenerationmentioning
confidence: 99%
“…In our study, we found no resident cells with GFP. Indeed, studies indicate that MSCs stimulate skeletal myoblast proliferation and differentiation via the release of paracrine factors such as S1P (sphingosine 1-phosphate) [26] or VEGF (vascular endothelial growth factor) [27]. …”
Section: Discussionmentioning
confidence: 99%